Popular Culture Informing Public Administration: Messages and Prospects for Social Equity. (4th May 2021) - McCandless, Sean; Elias, Nicole M.
Abstract : In the discipline of public administration, popular culture remains under-examined in scholarship and under-utilized in pedagogy. However, the field would benefit from greater integration of popular culture to expand understandings of governance, especially in that it provides important representations of and messaging about some of today's most pressing social equity issues. To contextualize popular culture in public administration, we use critical discourse analysis as a frame to demonstrate how popular culture can inform public administration, especially regarding social equity. We argue that popular culture should be more extensively covered in public administration, because it offers a lens for better understanding intersections of power, equity, and ethics in government.